(untitled) (Sains Humanika, 2013)
Taking into account the customers, supplier and organization involvement in the new product development (NPD), this article focuses on the synthesis, evaluation, and selection of various sub-factors of concurrent engineering involved in new product development process. The aim of this study was to provide the reliability and validity of six sub-factors of concurrent engineering model of the 49-item questionnaire and to analyze its association with concurrent engineering and new product development process in a sample of 35 manufacturing and services organization located in Johor, Malaysia. Methods: A self reported survey was conducted in 35 manufacturing and services organization located in Johor, Malaysia. Results: Appropriate internal consistencies of the six sub-scales: customers relationship, team development, continuity, tools and techniques, suppliers involvement and corporate focus and their association with concurrent engineering, were obtained. Zero-order correlation and regressions analysis replicated the theoretically assumed structure of the effective concurrent engineering (ECE). Evidence of criterion validity was obtained from cross-correlations of the scales and from their linear and multiple regression analysis. Finally, all seven scales were associated with a highly significant ratio of concurrent engineering as predicted by fundamental theory. Conclusion: Based on the results of this study the seven version of the model, questionnaire is considered a reliable and valid instrument for measuring association in developing the new complex product development process.